Mannose-functionalization of reconstituted high-density lipoprotein nanoparticles improves payload delivery and enhances M2-to-M1 phenotype reprogramming of RAW 264.7 macrophages polarized by B16-F10 melanoma cells - Dossou, Akpedje S.; Mantsch, Morgan E.; Sabnis, Nirupama; Berg, Rance E.; Fudala, Rafal; Lacko, Andras G. (Frontiers in Drug Delivery, 2023)
The targeting and conversion of the immunosuppressive (M2) tumor-associated macrophages (TAMs) to an immunostimulatory (M1) phenotype can induce tumor regression in advanced melanoma. We have previously characterized and reported the ability of reconstituted high-density lipoprotein nanoparticles (rHDL NPs) functionalized with DSPE-PEG-mannose (DPM) to deliver payload to macrophages. Herein, we investigate the modulation of macrophage phenotype and payload delivery mechanisms of the rHDL-DPM NPs in RAW 264.7 murine macrophages exposed to the conditioned medium (CM) from murine B16-F10 melanoma cells. The rHDL-DPM NPs loaded with the Stimulator of Interferon genes agonist, DMXAA, reduced protein levels of M2 markers. Through the mannose moiety, the rHDL-DPM-DMXAA NPs enhanced the production of interferon β and CXCL10 compared to the free DMXAA in the B16-F10 CM-educated RAW 264.7 macrophages. Compared to their non-mannosylated counterpart, the rHDL-DPM NPs delivered their payload more efficiently to the B16-F10 CM-educated RAW 264.7 macrophages. Mechanistically, both the scavenger receptor type B class 1 (SR-B1) and the mannose receptor (CD206) facilitated payload delivery to the macrophages via endocytic and non-endocytic mechanisms. Finally, the CM from rHDL-DPM-DMXAA NPs -treated macrophages enhanced paclitaxel (paclitaxel)-mediated cytotoxicity in B16-F10 cells. Together, these in vitro findings demonstrate the potential of the mannose-functionalized rHDL NPs in improving the targeting of M2-like TAMs and treatment outcomes when combined with immunotherapy or PTX in B16-F10 melanoma in vivo models.